Student teachers’ evaluative beliefs and quality criteria concerning a digital learning and test environment for the didactics of algebra - Beste, Meeri-Liisa; Wolff, Bianca; Girnat, Boris; Veith, Joaquin (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The subject of this article is the evaluation of the test format that will be integrated into a digital self-learning platform in the future. On the basis of a qualitative preliminary study and taking into account motivation theories, a questionnaire was developed for the evaluation, which records the quality characteristics of the test formats as a self-assessment of the participants at four measurement points in the associated course. The data were analysed using a longitudinal study and exploratory cluster analysis. Surprisingly, there were no significant changes in the assessment of the quality of the test environment, even though test scores declined. Thus, the digital test environment seems to be perceived positively regardless of performance. The cluster analysis yields a solution with two clusters: a large cluster containing the participants with consistently high test scores and a small cluster in which the test scores (strongly) decrease during the four measurement points. It is noteworthy that the two clusters hardly differ in their positive assessment of the digital examination format